2001
DOI: 10.1038/sj.gt.3301484
|View full text |Cite
|
Sign up to set email alerts
|

Electrotransfer of naked DNA in the skeletal muscles of animal models of muscular dystrophies

Abstract: The electrotransfer of naked DNA has recently been adapted to the transduction of skeletal muscle fibers. We investigated the short-and long-term efficacy of this methodology in wild-type animals and in mouse models of congenital muscular dystrophy (dy/dy, dy 2J /dy 2J ), or Duchenne muscular dystrophy (mdx/mdx). Using a reporter construct, the short-term efficacy of fiber transduction reached 40% and was similar in wild-type, dy/dy and dy 2J /dy 2J animals, indicating that ongoing muscle fibrosis was not a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 69 publications
1
50
0
2
Order By: Relevance
“…Recently, the use of electroporation to introduce plasmids into muscle has increased gene transfer efficiency, 25 including delivery of full-length dystrophin into the skeletal muscle of mdx mice. 20,34,35 For viral-based delivery, adenoviral vectors have been engineered with deletion of all viral sequences, except for those required for packaging of the virus. These so-called 'gutted' adenoviruses have a high cloning capacity and are able to accommodate the full-length dystrophin cDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of electroporation to introduce plasmids into muscle has increased gene transfer efficiency, 25 including delivery of full-length dystrophin into the skeletal muscle of mdx mice. 20,34,35 For viral-based delivery, adenoviral vectors have been engineered with deletion of all viral sequences, except for those required for packaging of the virus. These so-called 'gutted' adenoviruses have a high cloning capacity and are able to accommodate the full-length dystrophin cDNA.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,13,18 Similarly, reports have shown that percentage of transfected fibres increases from 1%, following the direct injection of plasmid DNA, to more than 10% 8,13 following electrotransfer. Recently, further improvements have been reported by Vilquin et al, 11 who achieved 37% transfection following multiple site injections and electrotransfer. In addition, it has also been shown that pretreatment of the muscle with hyaluronidase followed by electrotransfer can result in significant improvements in plasmid gene transfer, 12,14 and that 50% levels of transfection in nondystrophic muscle can routinely be achieved in our hands.…”
Section: Plasmid Gene Transfermentioning
confidence: 93%
“…[8][9][10] Electrotransfer-mediated plasmid gene therapy is being investigated for a variety of nonmuscle and muscle diseases, including muscular dystrophies such as Duchenne's muscular dystrophy (DMD) and congenital muscular dystrophy (CMD). 11 For any gene therapy protocol for DMD to be clinically relevant, the number of transfected fibres within a muscle is critical. However, the process of electrotransfer has been demonstrated to induce muscle damage.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some applications of ET now envisioned are the endogenous synthesis of EPO, 2 of the soluble receptor to TNFa 3 and of the antiinflammatory cytokine IL-10, 4,5 as well as tumour gene therapy, 6,7 restoration of muscle structural proteins, 8 and DNA vaccination. 9 ET is also applied to tumour electrochemotherapy, 10 where protocols with high voltage and short duration pulses allow antitumoral drugs to be locally delivered to tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…A now classical protocol proposed by Mir et al, 11 validated by several studies using either histological detection of b-galactosidase or quantification of light emitted by luciferase, has been applied successfully to therapeutic gene transfer in mouse muscle, its efficiency being evidenced from histological detection of locally expressed gene products 8 or from their physiological effect. 17 In optimized conditions, 18 this protocol has been shown to cause minimal adverse effects, as appreciated by morphology.…”
Section: Introductionmentioning
confidence: 99%